Neuroticism Modulates the Functional Connectivity From Amygdala to Frontal Networks in Females When Avoiding Emotional Negative Pictures - Deng, Yaling; Li, Shijia; Zhou, Renlai; Walter, Martin (Frontiers in Behavioral Neuroscience, 2019)
Amygdala activity was previously found to correlate with neuroticism as an effect of valence, but so far few studies have focused on motivational context. The network subserving altered amygdala activity has not yet been investigated although some studies showed strong effective connections with prefrontal cortex. The goal of this study was to test the modulatory role of neuroticism on the functional connectivity (FC) between amygdala and other brain regions, especially prefrontal cortex, during emotion processing from motivational direction. We applied an emotional picture viewing paradigm with different motivational directions (approaching and avoiding) in a large participant sample. The results showed that neuroticism predicted the amount of amygdala FC to dorsomedial prefrontal cortex (dmPFC) and middle cingulate cortex (MCC). Increased FC during negative versus positive pictures was found primarily in low neuroticism subjects, especially during the avoid condition. This valence and motivation dependent connectivity increase was disrupted for high neurotic participants. No effect of neuroticism was found for the approach condition. We showed that neuroticism, especially in the context of passive affect regulation, may have impaired connectivity between amygdala and putative regulatory cortical networks.